Incidencia de los precios del petróleo en el crecimiento económico a nivel mundial; un análisis con datos de panel, período 1995-2020. - Zhiñin Paqui, Marco Gustavo (2023)
The economic growth of countries has been conditioned by fluctuations in oil prices due to the fact that this non-renewable resource is the most traded internationally in terms of value and volume. In this context, the main objective is to analyze and evaluate the impact of oil prices on world economic growth through a statistical-econometric analysis for the period 1995 to 2020, by means of the GLS (generalized least squares) model, the Granger causality test that evaluates the impact and the Westerlund test (2007) that allows determining the long- term relationship. The information was obtained from the World Bank (2020) and the Federal Reserve Economic Data (2020). The results obtained show that there is a direct relationship between oil prices and GDP per capita in the global sample and for the groups of countries according to their income level LICs (Low Income Countries), MICs (Middle Income Countries) and HICs (High Income Countries), unidirectional causality was also found between oil prices and GDP per capita, the same that are cointegrated in the long run. While the control variables (gross fixed capital formation, unemployment, inflation) were found to be significant in the overall model and for the different groups of countries, with the exception of gross capital formation, which was not significant in the HICs group. Therefore, it is recommended for LICs and MICs to diversify their economies, promote investment in capital and technology, and maintain economic policy stability, while for HICs, technology transfer and technical assistance cooperation are recommended for LICs and MICs.